KINERJA KEPALA MANDRASAH TSANAWIYAH NEGERI TANJUNG LAUT KECAMATAN TANJUNG LUBUK KABUPATEN OGAN KOMERING ILIR DALAM MENGEFEKTIFKAN PROSES PEMBELAJARAN - Ibrahim Ibrahim (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2014)
AbstractPerformance headmaster has been going well, it can be seen from the interviews that the headmaster had duties and obligations as ideally headmaster duties properly, such as the headmaster had a good work program was short, medium, and long, always carry out the evaluation to the learning process, but there are some obstacles faced by educational institutions in effecting the learning process, including the lack of existing infrastructure, lack of teachers according to their academic qualifications, so the effect on the learning process. Keywords: Performance Principals and Effective Learning Process